Land and schooling transferring wealth across generations - Castillo, Gelia T. (The Philippine Review of Economics, 2004)
Although this book is not easy reading, if one is able to proceed patiently, the rewards to one's understanding of social change are ample even for a noneconomist, non-gender specialist but agriculturally-oriented social scientist. The authors' comment that 'although topics such as inheritance and family structure have long been studied by anthropologists, ethnographers and sociologists, past research has been primarily descriptive, which has made generalization and replication difficult' is well taken. Perhaps the value of such descriptive studies is that they have long been done and have provided the impetus for hypothesis formulation and testing. Nevertheless, even with their descriptive nature, patterns of similarities and differences across cultures and sites are already identifiable. Admittedly, though, quantification defines magnitudes of trends more 'precisely'. Land and Schooling, therefore, takes us much, much further into the specificities of how agriculture and rural society are evolving in the Philippines, Indonesia, and Ghana.